Not to Knot a Catheter. Case Report of the Knotting of a Suprapubic Catheter - S. A. Farook; U. Kariholu; G. Kousidis; M. Powlis (The Scientific World Journal)
A 20-month-old boy, who underwent left nephrectomy, had a suprapubic catheter inserted that knotted within the bladder. This case report identifies possible causes for such occurrences and how best to manage them.